Concurrent bullatine A enhances morphine antinociception and inhibits morphine antinociceptive tolerance by indirect activation of spinal κ-opioid receptors. (20th January 2017) - Huang, Qian; Sun, Ming-Li; Chen, Yuan; Li, Xin-Yan; Wang, Yong-Xiang
Abstract: Ethnopharmacological relevance: Bullatine A, a C20 -diterpenoid alkaloid and one of the major effective ingredients in Aconiti brachypodi Radix (Xue-shang-yi-zhi-hao), can block pain hypersensitivity in a variety of rodent models through expression of spinal microglial dynorphin A. Aim of the study: To assess the interaction between bullatine A and morphine on antinociception in acute nociception and pain hypersensitivity states, with the exogenous synthetic dynorphin A as a comparison Materials and methods: Spinal nerve ligation-induced neuropathic rats and naïve mice were used for assessing the acute and chronic interactions of bullatine A/dynorphin A with morphine. Results: Single subcutaneous injection of bullatine A or dynorphin A(1−17) did not either alter formalin- and thermally (hot-plate and water immersion tests)-induced acute nociception or potentiate morphine antinociception in naïve mice. In contrast, bullatine A dose-dependently inhibited formalin-induced tonic pain with the efficacy of 54% inhibition and the half-effective dose of 0.9 mg/kg. Concurrent bullatine A additively enhanced morphine antinociception. In neuropathic rats, the antinociceptive effects of multiple bidaily intrathecal injections of bullatine A and dynorphin A remained consistent over 13 days, whereas morphine produced progressive and complete tolerance to antinociception, which was completely inhibited by concurrent bullatine A and dynorphin A. A single intrathecal injection of bullatine A and dynorphin A immediately reversed established morphine tolerance in neuropathic rats, although the blockade was a less degree in the thermally induced mouse acute nociceptive tests. The inhibitory effects of bullatine A and dynorphin A on morphine tolerance were immediately and completely attenuated by intrathecal dynorphin A antibody and/or selective κ-opioid receptor antagonist GNTI. Conclusion: These results suggest that bullatine A produces antinociception without induction of tolerance and inhibits morphine antinociceptive tolerance, and provide pharmacological basis for concurrent bullatine A and morphine treatment for chronic pain and morphine analgesic tolerance. Graphical abstract: Highlights: Acute bullatine A and dynorphin A additively enhance morphine antinociception. Chronic bullatine A and dynorphin A induce no antinociceptive tolerance. Concurrent bullatine A and dynorphin A inhibit morphine antinociceptive tolerance. Bullatine A antinociception/anti-tolerance are mediated by spinal microglial dynorphin secretion. Our data provide basis for concurrent use of aconitines and morphine in analgesia.